2002
DOI: 10.1590/s0034-70942002000600013
|View full text |Cite
|
Sign up to set email alerts
|

Padrões de ventilação em anestesia: estudo retrospectivo

Abstract: Justificativa e Objetivos IMC < 20 com 10,74 ± 1,39;67 ± 1,08;54 ± 1,09; IMC > 30 com 7,86 ± 1,26 (p < 0,001, ANOVA) . Não houve diferença entre esses grupos para a freqüência respiratória instalada. No momento dos registros, homens (n = 123) e mulheres (n = 117) apresentaram semelhantes SpO 2 e P ET CO 2 . O IMC foi semelhante em ambos os grupos. Utilizou-se pressão positiva no final da expiração (PEEP) em 78 dos procedimentos (33%). Conclusões

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 6 publications
0
7
0
6
Order By: Relevance
“…This leads us to believe that intraoperative factors were the main cause of alterations in mechanical respiration in the immediate postoperative period. Mechanical ventilation of patients with obstructions in the intraoperative period with low flow volumes and low PEEP levels, avoids hyperinsufflation and auto-PEEP processes; but, favors the formation of atelectasis and ventilation-perfusion disorders [17]. This fact would explain the reduction of the compliance in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…This leads us to believe that intraoperative factors were the main cause of alterations in mechanical respiration in the immediate postoperative period. Mechanical ventilation of patients with obstructions in the intraoperative period with low flow volumes and low PEEP levels, avoids hyperinsufflation and auto-PEEP processes; but, favors the formation of atelectasis and ventilation-perfusion disorders [17]. This fact would explain the reduction of the compliance in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Almost half of patients needed some therapy to reverse hypoxemia such as alveolar recruitment, PEEP level elevation or oxygen therapy [20]. Laizo et al [21] analyzed complications that increased ICU lengh of stay and found as cause those related to pulmonary function (COPD and smoking, pulmonary congestion, prolonged mechanical ventilation), besides infections, kidney failure, stroke and hemodynamic instability (as arterial hypotension, arrhythmia and AMI).…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative hypoxemia is ascribed to poor gas distribution due to changed pulmonary volumes and respiratory system mechanical properties, and ventilatory control. (25) According to Ramos et al (26) general anesthesia causes several respiratory physiological effects as: atelectasis formation, residual functional capacity (RFC) reduction, ventilation-perfusion ratio change, and mucociliary function impairment. (26) Anesthesia may also promote respiratory system complacency reduction and increased gases flow airway resistance, from reduced pulmonary volume.…”
Section: Cardiac Surgery Postoperative Period Respiratory Failurementioning
confidence: 99%
“…These findings indicate that postoperative pulmonary complications may onset even during anesthesia. (25) Positive pressure mechanical ventilation hemodynamical changes…”
Section: Cardiac Surgery Postoperative Period Respiratory Failurementioning
confidence: 99%
See 1 more Smart Citation